ANALYSIS OF E-MODULE DESIGN DEVELOPMENT NEEDS ON GRADE VI ELEMENTARY SCHOOL MATH LEARNING - Toyib Bikoir; Indri Astuti; Dede Suratman (Sean Institute, 2022)
Abstract The general objectives of this research are to analyze the need for the development of e-module design in grade VI elementary school mathematics learning. Mathematics learning in elementary schools is a learning that requires strategies and media as well as concrete and interesting teaching materials. Moreover, in the era of increasingly advanced technological advances, educators must be able to adjust the situation by presenting innovative methods and media and teaching materials, in order to create an interesting, innovative and effective learning atmosphere. With a qualitative descriptive method, it is hoped that it will be able to analyze the needs in the development of the mathematical e-module design. Teaching materials in the form of e-mathematics modules are a form of adapting media and teaching materials in accordance with technological advances in the world of education. The advantages of e-modules include easy-to-use e-modules that are not limited by time and space, e-modules are more attractive because they can be accessed using Android laptops and cellphones. By using e-modules as teaching materials, students can learn in a guided and independent way both at school and at home. From the needs analysis as a first step in designing and developing teaching materials in the form of e-modules, it can be concluded that 60% of 25 students are happy with the learning model that students do independently, 65% of 25 students are proficient in using laptops and tablets, 80% laptops and tablets. school tablets as school infrastructure facilities are available, 55% of 25 students are happy in learning mathematics.